Analisis Promosi Pariwisata Pada Dinas Pariwisata Dalam Meningkatkan Kunjungan Wisatawan Ke Toraja Utara - Ika Kendek; Isak Pasulu; Abedneigo.C. Rambulangi (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2023)
This research aims to find out what promotions are used by the North Toraja Tourism Office to increase tourist visits. This research uses a qualitative approach as a research procedure which produces descriptive data in the form of written words and not numbers. The results of this research are achievements for tourism development in North Toraja, promotion includes: a) Advertising, by placing tourism advertisement containing notifications about tourism regarding the natural beauty and culture of North Toraja. b) Sales Promotion, carried out through exhibitions or events. c) Public Relations, carried out in collaboration with organizations or agencies and companies operating in the tourism sector such as ASITA, HPI and PHRI institutions. d) Direct Marketing, carried out through online channels.